The Impact of Fiscal Policy on Economic Growth In The Southern Africa Region: A Spatial Econometric Approach - Tseladikae, Katlego; Sinha, Narain; Kahaka, Zibanani (Departemen Ilmu Administrasi FISIP UNHAS, 2024)
This study investigates the spatial relationship between fiscal policy and economic growth across twelve member states of the Southern African Development Community (SADC) between 2000 and 2017. Utilizing spatial econometric techniques, the analysis reveals significant interdependence among member countries, particularly in the effect of tax revenues, which negatively impact the economic growth of neighboring states—suggesting the presence of harmful tax competition. While government expenditures show a positive but statistically insignificant impact on growth, the study identifies fiscal policy spillovers as a critical factor shaping regional outcomes. The absence of spatial dependence in public debt distribution further indicates that debt accumulation strategies remain largely country-specific. These findings underscore the need for coordinated regional fiscal frameworks, particularly in tax harmonization, to mitigate cross-border distortions and foster collective economic resilience. The study offers practical insights for enhancing regional integration and advancing shared development goals, especially in light of growing fiscal pressures and the pursuit of sustainable growth in post-pandemic contexts.